A Robust Design for Cellular Vehicles of Gold Nanorods for Multimodal Imaging. (6th June 2016) - Ratto, Fulvio; Centi, Sonia; Avigo, Cinzia; Borri, Claudia; Tatini, Francesca; Cavigli, Lucia; Kusmic, Claudia; Lelli, Beatrice; Lai, Sarah; Colagrande, Stefano; Faita, Francesco; Menichetti, Luca; et al.
Abstract : The pursuit of more selectivity in the delivery of plasmonic particles to tumors is critical before their penetration into clinical applications as the photoacoustic imaging and the photothermal ablation of cancer. As their direct infusion into the bloodstream remains problematic, due to a multitude of biological barriers, the development of alternative approaches is emerging as a new challenge. In this context, the recruitment of homologous tumor‐tropic cells that may serve as Trojan horses stands out as a fascinating possibility. Here, a novel model of gold nanorods is presented that feature a composite shell and undergo efficient and reproducible endocytic uptake from murine macrophages, which is fine‐tunable over a broad range of conditions. These cells preserve their viability and more than 90% of their innate chemotactic behavior in vitro, even with a cargo exceeding 200 000 particles per cell. In addition, we show that these vehicles are detectible by photoacoustic imaging down to concentrations in the order of 1% in whole blood and by clinical X‐ray computed tomography below 10%, which is within the typical fraction of a leukocytic infiltrate in a tumor microenvironment, and may even work as contrast agents for the photothermal ablation of cancer. Abstract : Hybrid particles with plasmonic bands in the near infrared are engineered to undergo consistent uptake from tumor‐tropic cells, without affecting their viability and chemotaxis. These cells may be recruited as Trojan horses to target tumors across all biological barriers and to enable their multimodal detection by photoacoustic imaging and X‐ray computed tomography and their destruction by photothermal ablation.